2008
DOI: 10.1111/j.1751-9020.2008.00151.x
|View full text |Cite
|
Sign up to set email alerts
|

The Authenticity of Self: Conceptualization, Personal Experience, and Practice

Abstract: Scholars across the social sciences often use the concept of authenticity to refer to such different things as sincerity, truthfulness, originality, and the feeling and practice of being true to one's self or others. Whereas the concept of authenticity refers to all of these things, a careful employment of this concept requires a clear understanding of it. By reviewing theory and empirical research on authenticity, we aim at a more precise conceptualization of authenticity. We argue that authenticity is about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(89 citation statements)
references
References 43 publications
(57 reference statements)
3
76
0
4
Order By: Relevance
“…The association of the relationship with self-esteem, continuity and distinctiveness may explain the centrality of this identity element. Individuals reported that they could construct a more "authentic" identity within their relationships as they were able to manifest their "private self" in an interpersonal context which was regarded as "safe" and trustworthy (Vannini & Franzese, 2008). For the first time, individuals felt increasingly at ease with their sexuality and were able to externalize gay-related cognitions and behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The association of the relationship with self-esteem, continuity and distinctiveness may explain the centrality of this identity element. Individuals reported that they could construct a more "authentic" identity within their relationships as they were able to manifest their "private self" in an interpersonal context which was regarded as "safe" and trustworthy (Vannini & Franzese, 2008). For the first time, individuals felt increasingly at ease with their sexuality and were able to externalize gay-related cognitions and behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The data suggested that some people simply failed to derive a sense of coherence between the identities that they projected in distinct contexts and thereby came to question the authenticity of their identities. Identity authenticity constitutes a key component of a positive sense of self (Vannini & Franzese, 2008) …”
Section: Grindr: Identity Enhancement or Threat?mentioning
confidence: 99%
“…BSA were allegedly viewed by SAS as temporary visitors to the homeland, which resulted in their exclusion from the ingroup. They were no longer regarded as "authentic" members of the ingroup (see Vannini and Franzese, 2008 for a discussion of authenticity in relation to identity), and were reportedly excluded from discussions about issues relevant to the village. Given respondents' continued identification with the homeland, this was threatening for identity.…”
Section: Migration and "Otherness"mentioning
confidence: 99%